Analisis Kinerja Keuangan, Corporate Governance, dan Corporate Social Responsibility pada Perusahaan Energi: Studi Kasus pada PT Medco Energi Internasional Tbk Periode 2020-2024 - Shania Asfi; Solihin Sidik; Venni Avionita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze financial performance, corporate governance, and corporate social responsibility at PT Medco Energi Internasional Tbk during the period 2020–2024. The research uses a descriptive method with quantitative and qualitative approaches based on secondary data obtained from financial statements, annual reports, and sustainability reports. Quantitative analysis includes financial ratios such as ROA, ROE, DAR, DER, TATO, and Inventory Turnover, while qualitative analysis reviews the implementation of corporate governance and corporate social responsibility. The results indicate that financial performance generally improved, corporate governance was implemented effectively, and corporate social responsibility contributed positively to corporate reputation and business sustainability.